2014
DOI: 10.1590/1983-1447.2014.04.45907
|View full text |Cite
|
Sign up to set email alerts
|

The formation of nurses in residency programs in public and private intensive care units

Abstract: A formação de enfermeiros residentes em UTI em instituição pública e privada La formación de enfermeros residentes en UCI en Instituciones públicas y privadasABSTRACT This qualitative study aimed to acknowledge the importance of practice in public and private institutions in the training of nurses in residency programs. Data were collected at two hospitals between February and March 2013, through interviews. From their analysis the following categories emerged: experience of graduate nurses in residency progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…The results of the analyses show a predominance of females (87.5%) among the graduates, a characteristic observed in the professional category of Nursing. In other studies carried out in Salvador, 12 Minas gerais 3 and Rio Grande do Sul, 13 were also found, with similar results, with females being the highest among the graduates. It is noteworthy that, even with the increase of male professionals in Nursing, started in the 90's, it is still an unimpressive number when compared to that of women, supported by the historical process that advocates it as an inherent activity for women.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The results of the analyses show a predominance of females (87.5%) among the graduates, a characteristic observed in the professional category of Nursing. In other studies carried out in Salvador, 12 Minas gerais 3 and Rio Grande do Sul, 13 were also found, with similar results, with females being the highest among the graduates. It is noteworthy that, even with the increase of male professionals in Nursing, started in the 90's, it is still an unimpressive number when compared to that of women, supported by the historical process that advocates it as an inherent activity for women.…”
Section: Resultssupporting
confidence: 70%
“…Similar results were observed in studies with nursing home graduates from the South of Brazil 17 and with students from the Intensive Care Nursing Residence of two public hospitals in the Northeast. 12 From these data, the perspective of the Residency programs, which propose the qualified insertion of young health professionals in the job market for better care is corroborated by this data. 6 In addition, it is common for recent graduates to seek early devices that provide professional maturation, facilitate their entry into the job market and seek to acquire skills and knowledge for which, the time for development at the undergraduate level has often been insufficient.…”
Section: Resultsmentioning
confidence: 59%
“…A criação e a implementação de protocolos, check-list ou diretrizes para o estabelecimento de padrões e normas com a finalidade de diminuir variações e dubiedade na prática assistencial é de extrema importância. Isto porque, tais instrumentos sistematizam a assistência de enfermagem, promovem maior segurança, qualidade do cuidado prestado e têm sido adotados nas instituições de saúde como estratégia para facilitar e controlar as atividades desenvolvidas pelos profissionais 16 . Os protocolos devem ser construídos com a participação de todos os envolvidos no processo de trabalho, pois existe uma tendência negativa na implementação de rotinas, em assumir caráter prescritivo e genérico e ser interpretada, pelos profissionais como mais uma atividade burocrática 16 .…”
Section: Importância Do Conhecimento Sobre Ritmos Cardíacosunclassified